The comparison of professional confidence in nursing students and clinical nurses: A cross-sectional study - Abbas Makarem; Fatemeh Heshmati-Nabavi; Laila Afshar; Shahram Yazdani; Zohre Pouresmail; Zohre Hoseinpour (Wolters Kluwer Medknow Publications, 2019)
Background: Achieving and improving professional confidence (PC) is an ongoing process from the studentship period to independent professional career. This study aimed to assess PC and compare it between nursing students (NS) and clinical nurses (CN). Materials and Methods: This cross-sectional study was conducted in a medical sciences university in an urban area of Iran in 2015. Nursing students (NS = 230) and clinical nurses (CN = 192) participated in this study. Data were collected through the nurses professional confidence scale (NPCS), consisting of 35 questions on PC. A six-point Likert scale was used for "never" to "always" corresponding to the score of 1-6. The analysis of variance, Pearson correlation, and Backward Multiple linear regressions were used for data analysis. Results: The mean (SD) standardized scores of PC in the NS and CN were 64.59 (11.06) and 73.63 (10.05). LSD test showed that the PC score of CN with work experience of 10-20 years was significantly higher than those with less than 10 years (mean difference = -4.25, p = 0.019). Also, the mean scores of PC in the NS in the fourth and fifth academic semesters (mean difference = 12.25, p < 0.001) were higher than that in the students in the third academic semester (mean difference = 10.09, p < 0.001). Conclusions: CN experiences a higher level of PC during the middle years of work, and NS in their middle years of studying. Creating a supportive environment for learning and working can help them to maintain PC.